Extraction and partial purification of antibacterial compounds from selected Malaysian plants - Erlina Abdullah (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
The screening practices for phytochemical compound from plants is essential to explore more natural sources to replace synthetic antibiotics which generally associated with multi-drug resistance as well as having side effects. In this study, screening of antibacterial property from 19 Malaysian flowering plants was conducted and optimization of the process conditions for extraction of antibacterial compounds was carried out as well. In addition, the purification of the antibacterial compound from potential plant was carried out. During the screening, the plants were extracted with methanol, ethyl acetate, hexane and distilled water. The crude extracts of each plant (5 mg/disc) were tested against Bacillus subtilis and Escherichia coli using agar disc diffusion assay method. The optimization study was carried out as designed by Face Centered Central Composite Design (FCCCD) using Design Expert 6.0.8 software and the parameters that were considered for optimization include agitation, temperature, and incubation time. The screening results showed that most of the plant samples extracted with methanol and ethyl acetate have positive activity toward B. subtilis growth but not E. coli. Ethyl acetate extract of S. cannifolium leaves showed the highest antibacterial activity (25.0 mm) and optimization of extraction process for antibacterial compounds was carried out using this plant. The best conditions postulated from optimization study are 9.58 hr, 300 rpm, and 27.35°C. S. cannifolium leaves were later extracted using these conditions to obtain extract to be purified for obtaining antibacterial compounds. For purification, open column chromatography was conducted and ethyl acetate, hexane and ethanol were used as the mobile phase. The results showed that the elution of column with 80% ethyl acetate in ethanol provide fractions with the highest antibacterial activity. The fractions were analyzed with TLC plates and revealed a single spot under UV light at 0.85 Rf value. HPLC analysis was performed to confirm the component appeared on the TLC plates. The result showed two isolated compounds at retention time of 5.53 min and 8.26 min. Identification and characterization of each isolated compound can be performed in future study by mass spectrometry and NMR. In conclusion, this study was able to purify the antibacterial compounds from S. cannifolium leaf extracted with ethyl acetate at optimum condition.